KAJIAN MA’ANIL HADIS MENGENAI ANJURAN MEMBUNUH CICAK - Nafiroh, Laylatun; Sahlan, Moh. Abdul Azis (Al-Bayan: Journal of Hadith Studies, 2023)
The diversity of flora and fauna is one of the signs of the power of Allah the Almighty in creating His creatures. In general, the Qur’an mentions six categories of beings created by Allah: inanimate objects, plants, animals, angels, jinn, and humans. Each of these beings has its own function and role in the order of existence. Islam teaches its followers to respect animals and preserve their lives. Furthermore, Allah also commands through revelations in the Qur’an that humans must always do good (ihsan) towards all living beings, including animals. However, there is a hadith that encourages the elimination of a particular animal called the lizard (al-wazagh). This creature is categorized as a fuwaisiq (harmful or nuisance animal), and its extermination is recommended. In fact, it is stated that there is a reward for killing it, depending on whether it is killed with one, two, or three strikes. This is explained in hadiths narrated by Abu Dawud, Muslim, Ahmad, and others. This study aims to investigate the meaning contained in the hadith that recommends killing lizards. The hadith that instructs the killing of lizards requires more serious examination. Many Muslims use this hadith as a basis for action in the hope of gaining rewards, yet they may not fully understand it in terms of its text, context, and application in the modern era. This research is a library-based study using a thematic (maudhu’i) approach, to explore the hadith that encourages the killing of lizards from textual, contextual, and contemporary perspectives, so that it can be properly understood. After analyzing the hadith that instructs the killing of lizards, several conclusions were found indicating that the Prophet ordered this action because lizards are considered to be disturbing or harmful animals. Certain types of lizards were believed to pose a risk to humans, especially by potentially spreading leprosy. This hadith becomes relevant as a basis for argument when the animal in question causes disturbance or poses a danger, for example, its droppings, which are often found on the floor, tables, chairs, or even on food. Health experts state that lizard droppings contain Escherichia coli bacteria, which can cause stomach issues, diarrhea, and food poisoning if someone consumes food contaminated by them.